Hoplonemertean larvae are planktonic predators that capture and devour active animal prey. Issue 1 (12th February 2022) - von Dassow, George; Mendes, Cecili B.; Robbins, Kara; Andrade, Sónia C. S.; Maslakova, Svetlana A.
Abstract: The superficially simple ciliated planktonic larvae of hoplonemerteans have been assumed to be lecithotrophic direct developers, even though many develop from such small eggs that it is hard to imagine how they could give rise to a viable juvenile without some phase of larval feeding. Indeed, attempts to raise such larvae to settlement without food invariably fail. Observations that some hoplonemertean larvae are found in plankton samples at a range of sizes, and much larger than hatchlings, suggest that they must indeed feed somehow. Because these so‐called planuliform larvae lack apparent means to concentrate suspended algae or other unicellular food, one alternative hypothesis is that they are planktonic predators that hunt large prey. Here we provide direct evidence that this is indeed the case for six distinct species of hoplonemerteans. We recorded wild‐caught larvae of Paranemertes californica, Paranemertes sp., Gurjanovella littoralis, Emplectonema viride, Carcinonemertes epialti, and Ototyphlonemertes sp. attacking, subduing, and devouring pelagic crustaceans, including barnacle nauplii, cyprids, copepods and their nauplii, and others. Although there is no doubt that some hoplonemerteans are genuine lecithotrophs, our evidence suggests that many species in this group both feed and grow during an extended planktonic larval period. This conclusion has important consequences for biogeographic and life history studies in this group, because it implies enhanced potential for long‐distance dispersal. More broadly, the possibility that many animal larvae are actually carnivores invites reconsideration of prevailing stereotypes about metazoan developmental modes and the trade‐offs between them.